Nairobi Eye: A Clinico-epidemiological Study from A Tertiary Care Center of Central Nepal - KC, Shekhar; Mishra, Aditi; KC, Dhiraj; Karn, Dharmendra (Journal of Lumbini Medical College, 2020)
Introduction: Periocular paederus dermatitis (Nairobi eye) is characterized by erythematous vesiculo-bullous linear plaque with stinging sensation. It commonly occurs during rainy season. It has been described in people living near agricultural fields due to the potential toxin pederin. This study aims to evaluate the demographic profile and clinical presentation of patients with periocular paederus dermatitis in a tertiary care center. Methods: This was a descriptive, cross-sectional study evaluating patients attending dermatology and/or ophthalmology department with features consistent with paederus dermatitis involving periocular area from June to August, 2019. Relevant demographic and clinical data were obtained; clinical photographs were taken and histopathology performed among selected patients. Results: A total of 24 (14.8%) patients had features of Nairobi eye among 162 patients of paederus dermatitis. Majority of the patients were males (1.4:1) with mean age 29.08±13.38 years. The peak time of presentation was the first week of July (37.5%). Mean time period between onset of symptoms and presentation was 3.41±2.01 days. The lesions were unilateral in all cases, with predominant involvement of the right eye (62%). Burning sensation (80%) and itching (60%) were the predominant symptoms while conjunctival hyperemia (41.6%), seropurulent discharge (20.8%) and chemosis (16.6%) were the ocular findings. Most of the patients (n=17, 70.8%) noticed the lesion while waking up in the morning. Conclusion: The finding of the present study has shown that Nairobi eye is a common presentation during rainy season. Periocular findings with significant intraocular signs were documented to be presenting features among patients with periocular paederus dermatitis.